(3OQhS aj GdGbJUGO GdSjGSjs - (3ScjfI(B, (3Hf MehOs ((3GdLRGFQ(B:s (3OGQ GdMOjK ddcJGH(B,s, 2014)
(3ehVhY h efgL GdGbJUGO GdSjGSj, GdacQ GdGbJUGOj dOi GHf NdOhf , GdJLGQjhf (B( (3GdeQcGfJjdjhf (B)(3, GdWHjYjhf (B( (3GdajRjhbQGW(B)(3, GdfXQjI GdJbdjOjI (B((3GdcdGSjcjI(B)(3, GdfXQjI GdeGQcSjI, GdfXQjI GdMOjI(B((3GdfjhcdGSjcjI(B) (3, GdacQ GdcjfRj, GdfbhO MSH GdcdGSjc h eGQcS h GdfjhcdGSjc, fXQjI GdSYQ MSH GdcdGSjc h eGQcS , GdGLhQ MSH GdcdGSjc h eGQcS h GdfjhcdGSjc, GdQjY MSH GdcdGSjc h eGQcS h GdfjhcdGSjc, GdQHM MSH GdcdGSjc h eGQcS h GdfjhcdGSjc , GdaGFOI MSH GdcdGSjc h cjfR(B. s
Keywords: (3GdGbJUGO GdcdGSjcjs; (3GdePGgH GdGbJUGOjIs